h - Ooi, Wei Tsang; Snoek, Cees G. M.; Tan, Hung Khoon; Ho, Chin-Kuan.; Huet, Benoit; Ngo, Chong-Wah.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 15th Pacific Rim Conference on Multimedia, PCM 2014, held in Kuching, Malaysia, in December 2014. The 35 revised full papers and 6 short papers presented were carefully reviewed and selected from 84 submissions. The papers cover a wide range of topics in the area of multimedia content analysis, multimedia signal processing and communications, and multimedia applications and services. They have been organized into topical sections on video coding, annotation, image and photo, applications, people, image analysis and processing under extra help, nearest neighbor, neural networks, and audio. Also included are sections with best papers and posters and demonstrations.
Region-Based Interactive Ranking Optimization for Person Re-identification -- Adaptive Tag Selection for Image Annotation -- Twitter Food Photo Mining and Analysis for One Hundred Kinds of Foods -- Improving Color Constancy with Internet Photo Collections -- A Background Modeling Scheme Based on High Efficiency Motion Classification for Surveillance Video Coding -- An Adaptive Perceptual Quantization Algorithm Based on Block-Level JND for Video Coding -- Improved Prediction Estimation Based H.264 to HEVC Intra Transcoding -- Unified VLSI Architecture of Motion Vector and Boundary Strength Parameter Decoder for 8K UHDTV HEVC Decoder -- Using Label Propagation to Get Confidence Map for Segmentation -- Image Region Labeling by Exploring Contextual Information of Visual Spatial and Semantic Concepts -- Manifold Regularized Multi-view Feature Selection for Web Image Annotation -- Semantic Concept Annotation of Consumer Videos at Frame-Level Using Audio -- Text Detection in Natural Scene Images with Stroke Width Clustering and Superpixel -- Sketch-Based Retrieval Using Content-Aware Hashing -- Pixel Granularity Template Matching Method for Screen Content Lossless Intra Picture -- Music Interaction on Mobile Phones -- Semantically Enhancing Multimedia Lifelog Events -- Haar-Like and HOG Fusion Based Object Tracking -- Noise Face Image Hallucination via Data-Driven Local Eigentransformation -- Lip Segmentation Based on Facial Complexion Template -- Saliency-Based Deformable Model for Pedestrian Detection -- Age Estimation Based on Convolutional Neural Network -- A Curvature Filter and Normal Clustering Based Approach to Detecting Cylinder on 3D Medical Model -- Image Compositing Based on Hierarchical Weighted Blending -- Multifold Concept Relationships Metrics -- A Comparison between Artificial Neural Network and Cascade-Correlation Neural Network in Concept Classification -- Location-Based Hierarchical Event Summary for Social Media Photos -- Towards Natural Gestures for Presentation Control Using Microsoft Kinect -- 3D-Spatial-Texture Bilateral Filter for Depth-Based 3D Video -- A System for Parking Lot Marking Detection -- Fast Search of Binary Codes with Distinctive Bits -- Data-Dependent Locality Sensitive Hashing -- Cosine Distance Metric Learning for Speaker Verification Using Large Margin Nearest Neighbor Method -- Anchor Shot Detection with Deep Neural Network -- Adaptation of ANN Based Video Stream QoE Prediction Model -- Leveraging Color Harmony and Spatial Context for Aesthetic Assessment of Photographs -- A Multi-exposure Fusion Method Based on Locality Properties -- Image Abstraction Using Anisotropic Diffusion Symmetric Nearest Neighbor Filter -- Reduction of Multichannel Sound System Based on Spherical Harmonics -- Automatic Multichannel Simplification with Low Impacts on Sound Pressure at Ears -- Acoustic Beamforming with Maximum SNR Criterion and Efficient Generalized Eigenvector Tracking.
Keywords: Computer science; Data mining; Multimedia information systems; User interfaces (Computer systems).; Image processing; Pattern recognition; Computer Science; Multimedia Information Systems; Information Systems Applications (incl. Internet).; Image Processing and Computer Vision; Pattern Recognition; Data Mining and Knowledge Discovery; User Interfaces and Human Computer Interaction; Electronic books